A Study on the Photoreaction of 2(5H)‐Furanones with Substituted Acetylenes: Evidence for a Mechanistic Reformulation. Issue 11 (8th January 2016) - Flores, Ramon; Font, Josep; Alibés, Ramon; Figueredo, Marta
Abstract: The photoreaction of 2(5 H )‐furanones with alkynes has been investigated. The complexity of this process is evidenced by the variety of isolated products, which have allowed disclosing interesting mechanistic aspects. When the reaction is performed in acetonitrile under direct excitation, in addition to the primary [2+2] cycloadducts, products derived from an 1, 3‐acyl shift rearrangement are also formed. For unsymmetrical alkynes, the rearrangement of the head‐to‐tail primary adducts produces new regioisomers and, when the starting furanone is chiral, this rearrangement inverts the relative anti/syn geometry of the primary cycloadducts. In the reactions performed in acetone under photosensitized conditions, rearranged products were never detected, supporting that the 1, 3‐acyl shift takes place from the singlet excited state S1 of the β, γ‐unsaturated lactone. When bis(trimethylsilyl)acetylene is used as the alkyne partner, the major photoproducts are monocyclic bis(trimethylsilyl)lactones. Abstract : Light up your chemistry : The photoreaction of 2(5 H )‐furanones with substituted alkynes was investigated and some interesting mechanistic aspects were unveiled (see scheme).